The relationship between vascular endothelial growth factor (VEGF) in the serum and drained dialysate with the quality of peritoneal dialysis and peritoneal membrane transport rates - Jovanović, Nataša Ž.; Žunić, Snežana S.; Trbojević-Stanković, Jasna B.; Laušević, Željko D.; Nešić, Dejan M.; Stojimirović, Biljana B. (Archives of Biological Sciences, 2019)
Paper description: Chronic exposure to glucose-based peritoneal dialysis (PD) solutions causes peritoneal injury as a result of upregulation of vascular endothelial growth factor (VEGF) with proinflammatory and proangiogenetic activities. Few studies have examined the in vivo effects of VEGF on the peritoneal membrane in humans. Observed significant inverse correlations between drained dialysate VEGF concentrations, residual diuresis and residual renal function at chronic PD onset point to the importance of preserved residual renal function in achieving VEGF clearance. The predictive value of drained dialysate VEGF in identifying patients with preserved transport characteristics of peritoneal membrane and efficacious long term PD maintenance is emphasized. Abstract: Vascular endothelial growth factor (VEGF), a powerful angiogenetic agent crucial for microvascular hyperpermeability and neoangiogenesis in the peritoneum, is associated with increased solute transport rates in chronic peritoneal dialysis (PD) patients. We investigated the correlation between serum and drained dialysate (dd) concentrations of VEGF and the transport characteristics of peritoneal membrane and dialysis quality in 20 patients with end-stage renal failure at the beginning and after six months of PD. The serum VEGF (sVEGF) concentration rose significantly (149.33±116.71 pg/mL vs 239.36±102.23 pg/mL; p=0.012) and ddVEGF concentration increased slightly (38.44±50.47 pg/mL vs 43.55±51.10 pg/mL) during the first 6 months of PD. At the beginning of chronic PD, ddVEGF concentrations correlated inversely with the peritoneal equilibrium test (PET) glucose (R=-0.565; p=0.009) and creatinine (R=-0.506; p=0.023) and residual renal function (RRF) (R=-0.691; p=0.001); sVEGF concentrations inversely correlated with PET creatinine (R=-0.457; p=0.043) and residual diuresis (RD) (R=-0.691; p=0.001). After 6 months of treatment, ddVEGF concentrations correlated directly with PETcreatinine (R=0.450; p=0.047), and inversely with RRF (R=-0.552; p=0.012) and residual renal weekly Kt/V (R=-0.488; p=0.029). The sVEGF concentration inversely correlated with RD (R=-0.589; p=0.006). High ddVEGF at the beginning of PD is predictive of adverse alterations of the peritoneal membrane, i.e. increased transport rate of glucose and creatinine. ddVEGF values may help to identify patients who will preserve adequate transport characteristics of the peritoneal membrane and maintain successful long-term PD. https://doi.org/10.2298/ABS181120061J Received: November 20, 2018; Revised: December 19, 2018; Accepted: December 22 2018; Published online: December 27, 2018 How to cite this article: Jovanović NŽ, Žunić SS, Trbojević-Stanković JB, Laušević ŽD, Nešić DM, Stojimirović BB. The relationship between vascular endothelial growth factor (VRGF) in the serum and drained dialysate with the quality of peritoneal dialysis and peritoneal membrane transport rates. Arch Biol Sci. 2018;71(1):187-94.